Product Line-Based Network Calculus Analysis in Vehicular Communications - Halikulov, Nurbek; Baron, Anna; Hielscher, Kai-Steffen; German, Reinhard (2025 International Conference on Computing, Networking and Communications (ICNC), 2025)
Train communication systems are essential in the approval and safety processes of railway operations. In computer and packet-switched environment, the Network Calculus (NC) provides a robust mathematical framework which is used for analyzing the boundaries in particular systems or networks. The application of the Pay Multiplexing Only Once (PMOO) methodology allows for the achievement of accurate solutions within NC. In the context of (complex) system development, the principle of Product Line Engineering (PLE) has emerged by leveraging reusability concepts. This strategy can be achieved through the use of components that can be reused and customised. The paper explores the intersection of NC and PLE, utilizing the former to model and evaluate the performance of train network through prospective addition of new devices and flows to the current system variant. We introduce a pattern-based method to predict and manage network performance metrics associated with deterministic end-to-end flow latency analysis of extended variants. We utilize the Disco Deterministic Network Calculator (DiscoDNC) framework to derive such deterministic flow delays by evaluating the network topology. The evaluations demonstrate that the worst-case characteristics of data flows can be computed efficiently, avoiding redundant recalculations across various network configuration
Keywords: Multiplexing; Communication systems; Calculus; Rail transportation; Mathematical models; Delays; Topology; Safety; Large-scale systems; Vehicle dynamics; Product Line Engineering; Network Calculus; Pay Multiplexing Only Once; Feed-forward Networks; DiscoDNC